Late 20th Century Indian Ocean Heat Content Gain Masked by Wind Forcing. Issue 22 (13th November 2020) - Ummenhofer, Caroline C.; Ryan, Svenja; England, Matthew H.; Scheinert, Markus; Wagner, Patrick; Biastoch, Arne; Böning, Claus W.
Abstract: Rapid increases in upper 700‐m Indian Ocean heat content (IOHC) since the 2000s have focused attention on its role during the recent global surface warming hiatus. Here, we use ocean model simulations to assess distinct multidecadal IOHC variations since the 1960s and explore the relative contributions from wind stress and buoyancy forcing regionally and with depth. Multidecadal wind forcing counteracted IOHC increases due to buoyancy forcing from the 1960s to the 1990s. Wind and buoyancy forcing contribute positively since the mid‐2000s, accounting for the drastic IOHC change. Distinct timing and structure of upper ocean temperature changes in the eastern and western Indian Ocean are linked to the pathway how multidecadal wind forcing associated with the Interdecadal Pacific Oscillation is transmitted and affects IOHC through local and remote winds. Progressive shoaling of the equatorial thermocline—of importance for low‐frequency variations in Indian Ocean Dipole occurrence—appears to be dominated by multidecadal variations in wind forcing. Plain Language Summary: Indian Ocean surface waters have warmed more than the tropical Atlantic or Pacific over the last 60 years. In contrast, the amount of heat stored in the upper 700 m of the Indian Ocean did not exhibit strong increases between 1960 and 2000, which is counter to temperature trends in other ocean regions across the globe. Only since the 2000s was rapid warming down to 700 m observed for the Indian Ocean. Using ocean model simulations, our study demonstrates that the unusual behavior of Indian Ocean temperatures over the last 60 years was mainly due to wind conditions: Two different pathways how winds can impact the upper ocean temperature structure in the Indian Ocean, either through the atmosphere or via an oceanic connection from the Pacific, are highlighted. In fact, wind trends during 1960–2000 counteracted additional heat input into the Indian Ocean due to an overall warming climate. These long‐term changes in the Indian Ocean temperature structure affect regional climate in surrounding countries; they are also of importance for predicting how the Indian Ocean will respond in the near future to a warming climate. Key Points: Multidecadal variations in Indian Ocean heat content exhibit distinct spatiotemporal signals regionally and with depth Winds counteracted (western) Indian Ocean heat content increase due to buoyancy forcing prior to the 2000s but contributed to the rapid rise since Progressive shoaling of the Indian Ocean thermocline appears to be dominated by multidecadal variation in wind forcing